The School Garden: A Social and Emotional Place - Pollin, Susan; Retzlaff-Fürst, Carolin (Frontiers in Psychology, 2021)
School gardens are part of many schools. Especially in primary schools, but also in secondary schools, they are used as a learning space and experience space for the pupils. Their importance for the development of cognitive and emotional-affective abilities of pupils is empirically well proven. It is also empirically well proven that exposure to nature has an influence on the prosocial behavior of children and adults. However, there is a lack of studies investigating the effect of the stay in the school garden on the social behavior of pupils in secondary class. To investigate whether a school garden is a good environment for social learning, a self-report study and standardized observations with sixth-grade pupils were carried out. Thus, the socially competent behavior of the pupils (communication and cooperation) and their emotions could be analyzed. In order to provide emotional access to the scientific content of biology lessons and to strengthen social learning, each pupil was responsible for their own plant and the group bed over a period of 10 weeks. The design of the lessons followed the principles of basic needs—competence, autonomy, and relatedness—of the Self Determination Theory. The observations were made during a 90-min class, in the school garden as well in the classroom. The 31 girls and 22 boys, aged 11–12 years, changed weekly between the garden and the classroom. Over 150 observations were made in the school garden (82) and in the classroom (68). In summary, pupils showed more socially competent behavior in school garden lessons than in classroom lessons. The school garden lessons, designed according to the basic needs, seem to create favorable incentives for social learning. Due to frequent social interactions, it can be assumed that learning activities in school gardens can promote emotional and social competence.